ANALISA LEMBAGA PRAPERADILAN SEBAGAI KONTROL TUGAS PENYIDIK DALAM PROSES PENEGAKAN HUKUM - Prajitno, Tatang (Sekolah Tinggi Ilmu Kepolisian, 2023)
The purpose of the Criminal Procedure Code is to find and obtain or at least approach the material truth, namely the complete truth of a criminal case by applying the provisions of the Criminal Procedure Code honestly and precisely, with the aim of finding out who the perpetrators can be charged with committing an offense. law, and then request an examination and a decision from the court to find out whether it is proven that a crime has been committed and whether the accused person can be blamed